RELATIONSHIP OF ADMINISTRATIVE LAW AND THE LAW REGULATING ADMINISTRATIVE PROCEEDINGS - Avagyan, Norayr (State and Law, 2022)
In this scientific article, the author analyzed the correlation of substantive and procedural rights in the context of administrative law.As a result, the author came to reasonable conclusions that Administrative law includes both substantive and procedural law, but in administrative law, procedural and legal norms and the relations regulated by them, as proper legal processes, are predominant and primary, as a guarantee of the protection of the right, which expresses the main feature of administrative law. Administrative proceedings, unlike other forms of administration, are subject to more stringent regulation, which is expressed in its structural and procedural aspects. The law regulating administrative proceedings expresses specificity with its strict regulation, which is expressed in the structural and procedural aspect.
Keywords: separate types of administrative proceedings; peculiarities of administrative proceedings; strict regulation of administrative proceedings; structural and procedural peculiarities